1989
DOI: 10.1149/1.2096739
|View full text |Cite
|
Sign up to set email alerts
|

Location Effects of Extended Defects on Electrical Properties of p+‐n Junction

Abstract: Ion implantation damage that transforms to crystallographic defects such as dislocation loops or stacking faults with heat-treatments is unavoidable in VLSI device fabrication. Dislocation loops were introduced into three different regions of p § junction such as the p § the depletion, or the n region by Si implantation followed by annealing. Stacking faults were introduced into the p § region or extended into the depletion region of p § junction by Si implantation followed by oxidation. Locations, densities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, when STI dislocations penetrate into the depletion region, they act as recombination/generation centers within the bandgap; thereby, an abnormally large leakage current of reverse-biased junction can flow through them. 14 Large local stress can produce trap centers that act as a source of junction leakage and induce parasitic leakage current. To closely investigate the effect of STI dislocations and sidewall stresses on the junction leakage current in STI processing, we evaluated the value of leakage current at 3.5 V in a 8 M cell array full area pattern.…”
Section: Resultsmentioning
confidence: 99%
“…However, when STI dislocations penetrate into the depletion region, they act as recombination/generation centers within the bandgap; thereby, an abnormally large leakage current of reverse-biased junction can flow through them. 14 Large local stress can produce trap centers that act as a source of junction leakage and induce parasitic leakage current. To closely investigate the effect of STI dislocations and sidewall stresses on the junction leakage current in STI processing, we evaluated the value of leakage current at 3.5 V in a 8 M cell array full area pattern.…”
Section: Resultsmentioning
confidence: 99%
“…The source of this rather strange modified dopant profile for the 1100 C sample is not clear at the moment. Ryoo et al 14 and Brotherton et al 13 have shown that dislocation loops which are located on the highly doped side of the junction do not contribute to the leakage current, whereas the DLs in the neutral region contribute significantly to leakage and the greatest leakage was obtained when the defects are located in the space charge region.…”
Section: Leakage Currents In the Presence Of Dislocation Loopsmentioning
confidence: 99%
“…Several studies have been published about the impact of the defect position on leakage currents, 13,14,[19][20][21] where the implant defects were located either inside the space charge region or in the highly doped side of the junction. In the work of Ryoo et al, 14 one of the investigated samples contained implant defects (loops) located in the neutral lowdoped region of the junction at 0 V bias. However, within the voltage range investigated in that work (0-100 V), a low bias (estimated at less than 10 V by the authors) was sufficient to incorporate the loops in the depletion region.…”
Section: -8mentioning
confidence: 99%
See 1 more Smart Citation
“…Extended defects resulting from pre‐amorphization processes and amorphizing implants are frequently reported to be related to increased leakage currents . Especially dislocation loops (DLs), {311} rod‐like defects and small interstitial clusters (ICs) are of growing interest.…”
Section: Introductionmentioning
confidence: 99%